A Systematic Review of the Effectiveness of Promoting Water Intake to Reduce Sugar-sweetened Beverage Consumption (P04-005-19) - Moghadam, Sepideh Dibay (Curr Dev Nutr, 2019)
OBJECTIVES: To examine whether promotion of water intake in the general population in and of itself reduces sugar-sweetened beverage (SSB) consumption independent from interventions that target SSBs. METHODS: Seven electronic databases were systematically searched: PubMed, Embase, PsycInfo, CINAHL Complete, Cochrane Central Register of Controlled Trials, CAB Direct, and Web of Science. The search hedge included concepts of drinking water, sweetened beverages, and clinical or controlled or longitudinal studies. Selected studies included a primary water promotion intervention and were published between 1 January 2000 and 6 January 2019, while those with more than a minimal SSB reduction intervention were excluded. We identified 5652 publications, chose 107 for full-text review and selected 17 for this review. Two authors independently extracted data using predefined data fields and rated study quality. RESULTS: Nine of the 17 studies were randomized controlled trials, six were non-randomized controlled trials, and two were single-group pre-post studies. Participants were primarily children and adolescents. Seven studies reported a decrease in sugar-sweetened beverage consumption. Among the eight studies that successfully increased water intake, five reported beneficial effects on SSB intake while three did not. Of the five positive studies, three were at serious or high risk of bias. Studies with decrease in sugar-sweetened beverage consumption tended to include a home-based or individually focused intervention. CONCLUSIONS: This review found little evidence that interventions aimed solely at increasing water consumption reduce sugar-sweetened beverage intake. Further research is needed to investigate whether interventions that combine water promotion and SSB reduction strategies could be synergistic for reducing SSB intake. SSB reduction approaches at this time should focus directly on SSBs. FUNDING SOURCES: Healthy Eating Research Program, Robert Wood Johnson Foundation.